Young children exploring probability – with focus on their documentations - Bommel, Jorryt van; Palmér, Hanna (NOMAD Nordic Studies in Mathematics Education, 2016)
This article reports on an intervention where possibilities and limitations with problem-solving as a basis for mathematics education in pre-school class were studied. In the article we explore how 50 children use non-guided documentation when working with a problem-solving task about probability. The results show that the task was possible to work with for these young children, and in the follow-up interviews many of the children seemed familiar with the mathematical concepts used, as well as with a relevant sample space. The children’s non-guided documentation showed a diversity of strategies and contributed positively to their exploration of probability, both during the lesson and in the final discussions.